2020
DOI: 10.2147/dmso.s245742
|View full text |Cite
|
Sign up to set email alerts
|

<p>Low Vitamin D Serum Level Is Associated with HDL-C Dyslipidemia and Increased Serum Thrombomodulin Levels of Insulin-Resistant Individuals</p>

Abstract: Background: Insulin-resistant individuals are known to have dyslipidemia and are predicted to be at high risk of cardiovascular events. Vitamin D deficiency was shown to be associated with dyslipidemia; however, the type of dyslipidemia associated with vitamin D deficiency in insulin-resistant individuals is not determined. Furthermore, there is evidence linking insulin resistance with low-grade inflammation suggesting levels of pro-inflammatory cytokines to be increased in insulin-resistant states. Objective:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
2
13
0
1
Order By: Relevance
“…Of note, it seems that the duration of diabetes rather than glycemic control is associated with VitD deficiency [ 26 ]. Remarkably, observational studies as well as preclinical data support that low VitD correlates with increased risk of hypertension, atherosclerosis, metabolic disorders, and low-grade inflammation, all of which are conditions that share endothelial dysfunction as a common element [ 27 , 28 , 29 ]. Accordingly, through the high-frequency ultrasonographic imaging of the brachial artery to assess endothelium-dependent flow-mediated vasodilation, it was demonstrated that VitD improves endothelial function in VitD-deficient subjects [ 30 ] and in patients with T2D and with low serum levels of VitD [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, it seems that the duration of diabetes rather than glycemic control is associated with VitD deficiency [ 26 ]. Remarkably, observational studies as well as preclinical data support that low VitD correlates with increased risk of hypertension, atherosclerosis, metabolic disorders, and low-grade inflammation, all of which are conditions that share endothelial dysfunction as a common element [ 27 , 28 , 29 ]. Accordingly, through the high-frequency ultrasonographic imaging of the brachial artery to assess endothelium-dependent flow-mediated vasodilation, it was demonstrated that VitD improves endothelial function in VitD-deficient subjects [ 30 ] and in patients with T2D and with low serum levels of VitD [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“… 52 Notably, the active form of vitamin D has both cardioprotective and pleiotropic effects and increases thrombomodulin and decreases tissue factor. 53 …”
Section: Discussionmentioning
confidence: 99%
“…52 Notably, the active form of vitamin D has both cardioprotective and pleiotropic effects and increases thrombomodulin and decreases tissue factor. 53 In line with our results on the systolic BP as a predictor of ACS, "The Third National Health and Nutrition Examination Survey" has reported a significant increase in the prevalence of hypertension [OR = 1.30, p < 0.001] in patients with low 25(OH)D (<21 ng/mL) compared to those patients with level more than 37 ng/mL. 54 In addition, a study confirmed the relationship between the TC, low-density lipoprotein cholesterol (LDL-C), HDL-C, and non-HDL-C and ACS vs control group.…”
Section: Discussionmentioning
confidence: 99%
“…13 The previous studies reported that the vitamin D deficiency may be associated with dyslipidaemia in apparently healthy people and in diabetic patients. [14][15][16] Besides, vitamin D deficiency was related to an increased risk of CVD. A meta-analysis of 24 observational studies indicated an inverse relationship between the vitamin D serum level and risk of CVD.…”
Section: Discussionmentioning
confidence: 99%